Life Cycle Assessment of an Integrated Direct Air Carbon Capture and Utilization System - Aliya Banu (17017731) (2025)
This article presents a thorough life cycle assessment (LCA) study on carbon capture and utilization (CCU) systems for low‐carbon fuel production. The process involves capturing carbon dioxide (CO2) from indoor environments using an integrated heating, ventilation, and air conditioning (HVAC)—direct air capture (DAC) unit, a technology crucial for mitigating climate change (CC). Integrating DAC with HVAC systems is highlighted for its potential to enhance energy efficiency and indoor air quality. Electrochemical reduction of CO2 to formic acid (FA) and Fischer–Tropsch processes are studied for carbon utilization. A sensitivity analysis was performed on the adsorbent type, electricity source, and water source. The environmental impacts were found to be 1.80 kg CO2 eq, 9.04 × 10−4 kg PM2.5 eq, 1.04 × 10−5 kg P eq, 2.95 × 10−3 kg SO2 eq, 0.36 kg 1,4 DB eq. for CC, fine particulate matter, freshwater eutrophication, terrestrial acidification, and terrestrial ecotoxicity, respectively, per kg FA produced. Using renewable energy can significantly lower the environmental impacts; the lowest value was obtained from integration with nuclear energy at 0.496 kg CO2 eq/kg FA. A specific Qatar case study was also performed for FA production with CO2 utilized from DAC‐HVAC. The paper highlights the environmental benefits of CCU, emphasizing its dual purpose of addressing CC and sustainable fuel production. This study represents a significant contribution to global initiatives for a more sustainable and carbon‐neutral future. Other Information Published in: Energy Science & Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ese3.70122